Share
Explore BrainMass

Multiplying-Out and Factoring (5 Problems)

1. Perform the indicated operations and simplify.

2{9x - 3[2x - 2(3x - 2 - 2x - 4) - 2] +5} =

2. Multiply out:

(5x - 4)3 =

Factor completely.

3. 36x3 - 100x =

4. 32x2 -60x + 27 =

5. 4x3 -4x2 -x + 1 =

Solution Preview

1. 2{9x - 3[2x - 2(3x - 2 - 2x - 4) - 2] +5} =
= 2{9x - 3[2x - 2(x-6)- 2] +5}
= 2{9x - 3[2x -2x +12 -2]+5}
= 2{9x -6x + 6x -30 +5}
= 2{9x -25}
= ...

Solution Summary

Problems involving Multiplying-Out and Factoring are solved.

$2.19